Variations in the fecal microbiota and their functions of Thoroughbred, Mongolian, and Hybrid horses - Wen, Xiaohui; Luo, Shengjun; Lv, Dianhong; Jia, Chunling; Zhou, Xiurong; Zhai, Qi; Xi, Li; Yang, Caijuan (Frontiers in Veterinary Science, 2022)
The horse gut is colonized by a rich and complex microbial community that has important roles in horse physiology, metabolism, nutrition, and immune functions. Fewer across-breed variations in horse gut microbial diversity have been illustrated. In this paper, the gut microbiota of Thoroughbred, Mongolian, and Hybrid horses (first filial generation (F1) of Mongolian (maternal) and Thoroughbred (paternal)) was studied by second-generation high-throughput sequencing technology. Differences in gut microbiota composition and function between breeds were determined using diversity and functional prediction analysis. The alpha diversity analysis showed that the gut of Thoroughbred horses had a more abundant and diverse microbiota, while the diversity of Hybrid horses was intermediate between Thoroughbred and Mongolian horses. Subsequent cluster analysis showed that Hybrid horses have a more similar microbiota composition to Mongolian horses. LEfSe analysis revealed that the bacterial biomarkers for Thoroughbred horses at the family level were Prevotellaceae, Rikenellaceae, Fibrobacteraceae, p_251_o5, Lactobacillaceae, and uncultured_bacterium_o_WCHB1_41; for Mongolian horses was Planococcaceae; for Hybrid horses were Moraxellaceae, Enterobacteriaceae and Ruminococcaceae. The functional prediction results indicated that the metabolic pathways differ significantly between the breeds. Regarding metabolism, the Hybrid horses had the lowest proportion of the carbohydrate metabolic pathways, while the energy metabolic pathway had the highest proportion. The abundance ratios of the remaining eight metabolic pathways in Hybrid horses were between Thoroughbred and Mongolian horses. In conclusion, the results of this study showed an association between horses breed and gut microbiota.